Violet and blue light amplification in Nd3+-doped fluoroindate glasses - Maciel, G. S.; Menezes, L. de S.; Araújo, Cid B. de; Messaddeq, Younes [UNESP] (AIP Publishing, 1999)
We report optical gain at 382 and 414 nm from Nd3+-doped fluroindate glasses after excitation with lasers operating either at 583 or 532 nm. Stimulated emission due to a frequency upconversion process results in increase of the emitted violet and blue light intensity and emission line narrowing. Large optical gain is measured by pump-probe spectroscopy using samples with various Nd3+ concentrations. © 1999 American Institute of Physics.